Distributed Reactive Power Control based Conservation Voltage Reduction in Active Distribution Systems - Emiroglu, Selcuk; Uyaroglu, Yilmaz; Ozdemir, Gulcihan (Universitatea Stefan cel Mare din Suceava, 2017)
This paper proposes a distributed reactive power control based approach to deploy Volt/VAr optimization (VVO) / Conservation Voltage Reduction (CVR) algorithm in a distribution network with distributed generations (DG) units and distribution static synchronous compensators (D-STATCOM). A three-phase VVO/CVR problem is formulated and the reactive power references of D-STATCOMs and DGs are determined in a distributed way by decomposing the VVO/CVR problem into voltage and reactive power control. The main purpose is to determine the coordination between voltage regulator (VR) and reactive power sources (Capacitors, D-STATCOMs and DGs) based on VVO/CVR. The study shows that the reactive power injection capability of DG units may play an important role in VVO/CVR. In addition, it is shown that the coordination of VR and reactive power sources does not only save more energy and power but also reduces the power losses. Moreover, the proposed VVO/CVR algorithm reduces the computational burden and finds fast solutions. To illustrate the effectiveness of the proposed method, the VVO/CVR is performed on the IEEE 13-node test system feeder considering unbalanced loading and line configurations. The tests are performed taking the practical voltage-dependent load modeling and different customer types into consideration to improve accuracy.
Keywords: energy conservation; Computer engineering. Computer hardware; voltage control; TK1-9971; TK7885-7895; Engineering; reactive power control; smart grids; Electrical engineering. Electronics. Nuclear engineering; renewable energy sources